Can public procurement be strategic? A future agenda proposition. Issue 4 (4th November 2019) - Guarnieri, Patricia; Gomes, Ricardo Corrêa
Abstract : Purpose: This paper aims to demonstrate how public procurement can be strategic. Design/methodology/approach: A systematic literature review (SLR) was conducted following the protocol from Pagani, Kovaleski and Resende (2015), called Methodi Ordinatio, to select the relevant literature on this topic. The analysis of papers selected was carried out following the procedures of categorical content analysis (Bardin, 1977). Findings: In all, 68 full papers were analyzed from Science Direct and Web of Science. The results present the main characteristics of publications analyzed and the authors propose some categories of strategic practices related to public procurement that are in turn related to: sustainability, partnerships and supplier management, information systems and technology and other issues. Research limitations/implications: The main limitations of this paper are: the publication period considered of the articles selected is from January 2012 to March 2017; the databases Science Direct and Web of Science are selected as the sources of articles; the Methodi Ordinatio is used as the basic protocol of the SLR and, consequently, the inclusion and exclusion criteria described in the steps of the protocol are used. Practical implications: Showing how the public procurement can be strategic, this paper highlights the benefits of best procurement practices; similarly, it highlights those practices adopted by the private sector, which can highly contribute to the creation of value in public services that are aligned with the concept of obtaining "the best value for money". Social implications: The incorporation of strategic practices in public procurement can result in the best expenditure of public resources and the reduction of corruption in the process of procurement. Originality/value: This paper contributes to synthesize the knowledge on strategic procurement, a topic exploited by few people in the public organizations. It differentiates from other literature reviews already published, considering that these studies do not deal, specifically, with public procurement and, also, do not use protocols of SLR. Moreover, this paper indicates a future agenda of research, which can aid researchers and practitioners acting in this field of knowledge.